DESIGN OF BED SADDLE OF HIGH-SPEED PRECISION CNC LATHE BASED ON TOPOLOGY OPTIMIZATION - DUAN MingDe; LI Yan; GU JiaJia; ZHANG ZhuangYa (Jixie qiangdu)
In order to meet the condition of high precision,efficiency and speed of modern NC machine tools and to improve the static,dynamic performance as well as lightweight design of their basic components,the design of bed saddle which is the key components of ADGM numerical control machine tool was optimized based on topology optimization method. Firstly,according to variable density method,which makes bed saddle quality be objective function and allows stiffness as well as natural frequency to be constraint condition was established,then the best structure layout of bed saddle was acquired as a result of topology optimization.Finally,the integral design of the bed saddle was accomplished,with the basis of best structure layout of bed saddle and the requirements of the reasonable design. Compared with the original design,new design reduces 13% of bed saddle’s weight,and the maximal displacement decreases 6%. Also,the first order natural frequency increases 8%,while the second order natural frequency increases 7%,and the third order natural frequency increases 6. 7%. The optimization result shows that the proposed method for bed saddle is feasible,thus providing the theoretical basis for the lathe’s basic components optimization design.